Subacute cutaneous lupus erythematosus. Issue 2 (9th June 2016) - Furzeland, Jacqueline; Malcolm, P
Abstract : A 31-year-old female soldier developed subacute cutaneous lupus erythematosus, which remained undiagnosed for 4 years. Referral to dermatology and a punch biopsy confirmed the diagnosis and effective treatment was instituted. The presence of an unresolving annular rash in light-exposed areas, especially in a young woman, should prompt thorough investigation and referral if necessary. The prognosis for this condition is generally good, although a small proportion of patients will go on to develop systemic lupus erythematosus. The occupational implications of this condition require thoughtful management in the military population.